The Effect of Company Size, Asset Growth, Asset Structure, Debt Level and Inventory Profitability - Br. Silitonga, Grace Angelia; Eny Purwaningsih (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study examines the impact of company size, asset growth, asset structure, debt level (DER), and inventory turnover on profitability (NPM) in the food and beverage subsector industry listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 reporting year. The background of this research is based on the importance of profitability for the continuity of the company and how internal and external factors affect the company's financial performance. The purpose of this research is to analyze the impact of company size. Using data from 25 companies listed on the Indonesia Stock Exchange, this study uses multiple linear regression analysis and hypothesis testing using SPSS statistical software. Based on the test findings, it is known that firm size has a positive impact on profitability, debt level has a negative impact on profitability, and asset growth, asset structure and inventory turnover have no impact on profitability. These results provide insight that companies should utilize size as a signal of stability, manage asset growth efficiently, balance asset structure, reduce dependence on excessive debt, and optimize inventory management according to market strategy to increase profitability and attractiveness to investors